PENGARUH PERBEDAAN FORMULA PUPUK PADA PERTUMBUHAN DAN HASIL KAILAN (Brassica oleracea) - Dewi Komala Sari; Made Deviani Duaja; Neliyati . . (Bioplantae, 2014)
This experiment aims to determine the effect of different fertilizers formula on chinesse kale (Brassica oleracea). This research was conducted at the experimental farm of the Faculty of Agriculture, University of Jambi. This research was carried out for 3 months. This study was conducted using Randomized Complete Block design with one factor of fertilizers formula. The treatments consist 6 treatment : Formula 1 = Chemical fertilizers (Urea: 200 kg / ha, Sp-36: 150 kg / ha and KCl: 150 kg / ha), Formula II = solid chicken manure 1.6 kg / plot, Formula III = solid chiken manure 3.2 kg / plot, Formula IV = Liquid fertilizer feremented from chicken manure 25 ml / plant, Formula V = Liquid fertilizer fermented from chicken manure 50 ml / plant, Formula IV = Liquid fertilizerfermented from chicken manure 75 ml/ plant. Each treatment was repeated four times. The results showed the formula II, solid chicken manure at dose 1.6 kg / plot achivied the highest chinese kale yield. Key words: Growth, Kale, Fertilizer, Chienese, chicken manure